Impact of linguistic problems on learning arabic speaking skills among non-native Arabic-speaking students - Wan Sulong, Wan Muhammad; Maming, Pabiyah; Hassan, Abd Rauf; Aljaer, Mansour Mabroukah Salim (Human Resource Management Academic Research Society, 2024)
This study investigates the impact of linguistic problems on the acquisition of speaking skills among non-native Arabic-speaking students at the International Islamic School in Gombak, Malaysia. It identifies key problems such as pronunciation difficulties, limited vocabulary, and grammar errors that hinder students' ability to communicate effectively in Arabic. A quantitative approach was used, employing descriptive analysis to explore these problems and their effects. Results indicate that students struggle particularly with linguistic problems such as pronunciation of specific Arabic sounds (e.g., 'ع' and 'غ') and understanding grammatical rules. The study emphasizes the importance of targeted training and supportive learning environments to address these problems. Recommendations include focused interventions on pronunciation, vocabulary-building activities, and the use of error analysis to guide teaching strategies, aimed at enhancing students' confidence and proficiency in speaking Arabic. Insights from this research can inform curriculum development and teaching methodologies, improving the learning outcomes for non-native speakers in similar educational contexts.